ERK1/2-PPARγ pathway is involved in Chlamydia pneumonia-induced human umbilical vein endothelial cell apoptosis through increased LOX-1 expression. (3rd March 2020) - Sun, Shan; Duan, Xiaoyu; Wu, Qinqin; He, Yingxia; Bu, Xiaofen; Ming, Xiaoyan; Yan, Fengqin; Zhu, Hong
Abstract: Chlamydia pneumonia ( C.pn ) is a common respiratory pathogen that is involved in human cardiovascular diseases and promotes the development of atherosclerosis in hyperlipidemic animal models. C.pn reportedly up-regulated lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) in endothelial cells. Recently, the anti-atherosclerotic activity of peroxisome proliferator-activated receptor γ (PPARγ) has been documented. In the present study, we investigated the effect of C.pn on LOX-1 expression in human umbilical vein endothelial cells (HUVECs) and identified the involvement of the PPARγ signaling pathway therein. The results showed that C.pn increased the expression of LOX-1 in HUVECs in a dose- and time-dependent manner. C.pn-induced up-regulation of LOX-1 was mediated by ERK1/2, whereas p38 MAPK and JNK had no effect on this process. C.pn induced apoptosis, inhibited cell proliferation, and decreased the expression PPARγ in HUVECs. Additionally, LOX-1 activity and cell injury caused by C.pn through activation of ERK1/2 was completely inhibited by rosiglitazone, a PPARγ agonist. In conclusion, we inferred that activation of PPARγ in HUVECs suppressed C.pn-induced LOX-1 expression and cell damage by inhibiting ERK1/2 signaling.